Restitution Mechanism for Rape Victims in Aceh: An Analysis of The Normative Shortcomings of Qanun Jinayat - Widodo, Widodo; Tongat, Tongat (Legality : Jurnal Ilmiah Hukum, 2026)
This research examines the restitution mechanism for rape victims in Aceh. The rules on restitution for rape victims set out under Article 51 of Qanun Jinayat in Aceh are intended to protect the victims; however, they are deemed ineffective, given that the restitution implemented by the judges of Mahkamah Syar’iyah only covered 6% of the total victims, 9% of the prosecutions by prosecutors. The victims have no chance of recovering from the physical injuries, psychological trauma, and social trauma. This article was written based on the use of normative legal research methods. Legal materials comprise legislation, Qanun, Mahkamah Syar’iyah rulings, and district court rulings. The research results were analysed in light of the concepts of justice in Islamic criminal law and feminist legal theory. The research results reveal several points to ponder: (a) regulating the minimum uqubat for restitution at 250 grams of pure gold calculated according to the cost spent on recovering the victim, as well as the principles of justice and the maslahat (public benefit) in the context of Islamic criminal law; (b) regulating the obligations of Mahkamah Syar’iyah judges in determining the losses that the aggrieved parties have to take, particularly in terms of setting the amount of uqubat restitution according to the studies on victimology and the theory of feminist law that prioritises gender equality. If the defendant lives in poverty (gharim), the restitution status shifts to a compensation obligation to be paid by the state through baitul mal. However, the defendant must serve a jail sentence instead of probation. Rule amendments are consistent with the concept of justice and legal certainty in Islamic criminal law. The findings of this research should expand access to justice for victims, without restricting judges' freedom to decide cases or violating the human rights of defendants facing financial difficulties, thereby narrowing criminal disparities.